PERAN GURU PENDAMPING PADA ANAK AUTIS KELAS VI DI SEKOLAH DASAR THEODORE 1 KECAMATAN BATU AMPAR KOTA BATAM - sulastri, sulastri - (Jurnal Dedikasi Pendidikan, 2022)
This study aims to examine the role of assistant teachers for autistic children in grade VI at Theodore 1 Elementary School, Batu Ampar District, Batam City. Design of research was qualitative research. Research informants include accompanying teachers, homeroom teachers and parents of autistic children. Data collection techniques include observation, interviews and documentation. The data analysis technique used descriptive qualitative analysis which included data collection, data reduction, data presentation, and drawing conclusions. Testing the validity of the data using triangulation. The results showed that the role of the assistant teacher included: (1) Coordinating and collaborating between and among education and education personnel, as well as the community. (2) Building a network with educational institutions. . (3) Develop academic instruments. (4) The accompanying teacher plays a role in drilling. (5) Develop a compesatory service program for students with special needs. (6) Implementing mentoring academic learning. (7) Providing special service assistance. (8) Special learning in the resource room for autistic children has not been implemented. (9) Implement compesatory services according to the special needs of students. (10) Provide continuous guidance. (11) Conduct case conferences. Thus, it is concluded that the accompanying teacher has carried out his role well to assist the autistic child.